Incidence, risk factors and clinical course of pyogenic spondylodiscitis patients with pulmonary embolism. - Dubinski, Daniel; Won, Sae-Yeon; Keil, Fee; Behmanesh, Bedjan; Dosch, Max; Baumgarten, Peter; Bernstock, Joshua D.; Seifert, Volker; Freiman, Thomas M.; Gessler, Florian (European Journal of Trauma & Emergency Surgery, 2022)
Purpose: In patients with pyogenic spondylodiscitis, surgery is considered the treatment of choice to conduct proper debridement, stabilise the spine and avoid extended bed rest, which in turn is a risk factor for complications such as deep vein thrombosis and pulmonary embolism. Methods: We conducted a retrospective clinical study with analysis of a group of 99 patients who had undergone treatment for pyogenic discitis at our institution between June 2012 and August 2017. Included parameters were age, sex, disease pattern, the presence of deep vein thrombosis, resuscitation, in-hospital mortality, present anticoagulation, preexisting comorbidities, tobacco abuse, body mass index, microbiological germ detection and laboratory results. Results: Among the analysed cohort, 12% of the treated patients for pyogenic spondylodiscitis suffered from a radiologically confirmed pulmonary embolism. Coronary heart disease (p < 0.01), female sex (p < 0.01), anticoagulation at admission (p < 0.01) and non-O blood type (p < 0.001) were associated with development of pulmonary embolism. Pulmonary embolism was significantly associated with resuscitation (p < 0.005) and deep vein thrombosis (p < 0.001). Neurosurgery was not associated with increased risk for pulmonary embolism compared to conservative-treated patients (p > 0.05). Conclusion: Surgery for pyogenic spondylodiscitis was not associated with an elevated risk of pulmonary embolism in our analysis. However, we describe several risk factors for pulmonary embolism in this vulnerable cohort. Prospective studies are necessary to improve prevention and postoperative management in patients with pyogenic spondylodiscitis.